Exposed - Scottoline, Lisa (New York : St. Martin's Press, 2017)
""Plot twists aplenty raise the stakes." --People Magazine A BATTLE FOR JUSTICE PITS PARTNER AGAINST PARTNER... Mary DiNunzio wants to represent her old friend Simon Pensiera, a sales rep who was wrongly fired by his company, but her partner Bennie Rosato represents the parent company. When she confronts Mary, explaining this is a conflict of interest, an epic battle of wills and legal strategy between the two ensues--ripping the law firm apart, forcing everyone to take sides and turning friend against friend. SOMETIMES LOYALTY CAN BE LETHAL"--
Kirkus Reviews
Publishers Weekly
Library Journal Prepub Alert
Kirkus Books of Special Note
Adult
Keywords: Rosato & Associates (Imaginary organization) -- Fiction; Women lawyers -- Fiction; Mystery fiction; Legal stories